Motivational Factors of School Personnel in Schools Affected by Volcanic Activities - Bibaro, Dolly Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the motivational factors of school personnel in schools affected by volcanic activities in Malilipot District, Division of Albay. Anchored on Maslow’s Hierarchy of Needs, Herzberg’s Two-Factor Theory, and the researcher-developed Disaster-Adaptive Motivation framework, the study determined the respondents’ demographic profile, level of motivation, motivational factors, and the relationships between selected profile variables and motivation. It employed a descriptive-analytical mixed-methods research design involving 200 teaching personnel from selected mainland elementary and secondary schools during School Year 2025–2026. Data were gathered using a self-designed and validated questionnaire and were analyzed using frequency, percentage, weighted mean, Pearson’s Chi-Square Test of Independence, and SPSS. Findings showed that most respondents were middle-aged, female, married, residing near their schools, bachelor’s degree holders, mid-level personnel, and within the early to middle stages of service. The overall motivation level was moderate, with a safe, supportive, and resourceful working environment and supportive colleagues emerging as the strongest motivators, while personal resilience and coping support ranked lowest. Significant relationships were found between civil status and leadership communication, highest educational attainment and distance from school, and distance from school with salary, incentives, benefits, and safe working environment. The study concluded that psychosocial support and resilience training are essential for sustaining teacher motivation in volcanic-risk areas. The study supports SDG 3, SDG 4, SDG 8, SDG 11, SDG 16, and SDG 17 by promoting educator well-being, educational continuity, decent work, disaster-resilient communities, institutional preparedness, and stakeholder collaboration. Its sustainability impact lies in strengthening educational, psychosocial, institutional, and community resilience through Project RESEED Albay.
Keywords: Disaster-Adaptive Motivation; Disaster Resilience; Malilipot District; Motivation; Project RESEED Albay; Psychosocial Support; School Personnel; Volcanic Activities